Multiple Primary Cancer: Genetic Pathomorphological Factors of Endometrial and Breast Cancer (Texas Journal of Medical Science, 2023)
In this article, the results of detailed research on the genetic pathomorphological factors of multiple primary cancers: endometrial and breast cancer are presented. Also, the article provides detailed information about breast cancer, which ranks first in the world according to the index of female scientists, the causes of breast cancer, and the use of a new approach to treatment. Our new ideas and opinions about the treatment of patients with the combined use of radiotherapy and chemotherapy are presented.